A model for coopetitive games - CARFÌ, David (Journal of Mathematical Economics and Finance; Vol 1 No 1 (2015): Volume I Issue 1(1) Winter 2015, 2015)
In the present introductory work we propose a survey of an original analytical model of coopet- itive game, conceived and introduced in 2009 by the author himself. Much of the material presented here has been already published in their complex, at di_erent stages of development, in numerous pa- pers, during the last 5 years. Here we explain the present state of the theory, in a virtually complete, organized and self-contained version. We also suggest here - after the presentation of the model - general types of feasible solutions - again in a coopetitive perspective - in the form of sophisticated bargaining solutions (in a rational decision theory context) viewed as reasonable mediations among the partially diverging interests driving the players of the coopetitive games themselves.